In vitro Assessment of the Adsorption Efficacy of Activated Charcoal versus Kaolin on some used Medications of Narrow Index of Safety - Asmaa Abdelaziz Mohamed; Firas Aziz Rahi; Amna F. Alberqdar; Aziz, Teeba Abdellatif (Iraqi Journal of Pharmaceutical Sciences, 2024)
The purpose of this study is to investigate the in vitro adsorption power of activated charcoal (AC), light kaolin (LK), and heavy kaolin (HK) at a concentration of 0.2% weight-per-volume (w/v) on high dosages (10 tablets) of a variety of medications that have a narrow safety index. This will be done by testing the adsorption capacity of the three types of kaolin at the same concentration. This list includes a variety of drugs, some of which are as follows: diazepam, metoclopramide, theophylline, digoxin, and diltiazem HCL. The test was done by dissolving the pharmaceuticals from their tablets in the presence of the adsorbents while using simulated gastric fluid as the medium. This was done in order to determine how well the medications would work in the stomach. This was done in order to ascertain whether or not the method in question was successful. In order to evaluate the efficacy of these adsorbents as antidotes to treat oral overdoses of these medicines and to determine the success of this process, the goal of this treatment was to find out whether or not this treatment was successful. Activated charcoal had the capability of virtually completely absorbing all of the drugs that were put through their paces. Diazepam, metoclopramide, digoxin, and theophylline were some of the medications that were involved. Diltiazem was another one of the medicines that were involved. Both the light and heavy versions of kaolin were only able to absorb a restricted quantity of the illicit substances. The other types of adsorbents that are utilized do not compare to the capabilities of activated charcoal when it comes to the absorption of chemicals.